2018
DOI: 10.1080/08916934.2018.1431776
|View full text |Cite
|
Sign up to set email alerts
|

Functional TSH receptor antibodies in children with autoimmune thyroid diseases

Abstract: In conclusion, TSI is prevalent in children with GD while the highest serum TSI levels were noted in children with AITD and orbitopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…This study demonstrated that TSAb is a sensitive, specific, reliable and reproducible biomarker for pediatric GD/GO and correlates well with disease severity and orbital disease. A further multicenter pediatric study confirmed the above results in European children with GD and GO [74]. Children with GD + GO were TSAb positive in 23/24 (95.8%) samples while children with thyroidal GD only were TSAb positive in 47/53 (88.7%) samples.…”
Section: Pediatric Gd/gosupporting
confidence: 68%
“…This study demonstrated that TSAb is a sensitive, specific, reliable and reproducible biomarker for pediatric GD/GO and correlates well with disease severity and orbital disease. A further multicenter pediatric study confirmed the above results in European children with GD and GO [74]. Children with GD + GO were TSAb positive in 23/24 (95.8%) samples while children with thyroidal GD only were TSAb positive in 47/53 (88.7%) samples.…”
Section: Pediatric Gd/gosupporting
confidence: 68%
“…In contrast, the highly sensitive cell-based bioassays [26][27][28][29][30][31][32][33] exclusively differentiate between the TSH-R-stimulating Ab (TSAb) and TSH-R-blocking Ab [34,35]. Also, TSAb is a highly sensitive and predictive biomarker for the extrathyroidal manifestations of GD [36][37][38][39][40][41][42] as well as a useful predictive measure of fetal or neonatal hyperthyroidism [43,44]. Finally, the incorporation and early utilization of TSAb into current diagnostic algorithms conferred a 46% shortened time to diagnosis of GD and a cost saving of 47% [45].…”
Section: Serologymentioning
confidence: 99%
“…Further, in euthyroid children with GO, TBII were positive in 24 of 31 (77%) children only, while TSI were detected in all subjects (both p = 0.016). Additionally, in a different trial ( 36 ), children with GD+GO displayed the highest titers of TSAb (SRR% 417±135) in comparison to GD only (SRR% 320±157). Additionally, hyperthyroid children with GD+GO displayed higher TSI levels compared to children with GD only (median SRR%, 481 vs. 395%, both p < 0.001).…”
Section: Clinical Relevance Of Tsab As a Biomarker For Gomentioning
confidence: 93%